Academic Dishonesty among College Students: Academic Motivation vs Contextual Factors - Shmeleva, Evgeniia; Semenova, Tatiana (Voprosy obrazovaniya / Educational Studies Moscow, 2019)
Academic dishonesty among college students is often associated with low academic motivation, which has been confirmed by multiple international findings. However, the role of academic motivation may be overestimated, as such studies do not normally control for contextual factors such as faculty and peer behavior. This study utilized the theoretical framework of Eric M. Anderman and Tamera B.Murdock to identify the factors of academic dishonesty and the self-determination theory of Edward L. Deci and Richard M. Ryan to measure academic motivation. Longitudinal data on students of four Russian universities participating in the Project 5–100 (N= 914) is used to measure the ability of academic motivation to predict academic cheating and plagiarism rates while controlling for contextual factors. Regression analysis shows that learning motivation becomes insignificant as a predictor as soon as perceived consequences and peer effects come into play. The best predictor of both plagiarism and cheating is students’ perception of contextual factors, i. e. perceived prevalence of relevant behaviors among peers. Unlike with cheating, plagiarism rates are not contingent on the probability of punishment.